Myopia, retirement planning and commitment - Holmes, C (2011)
Decisions made by individuals planning for retirement may be myopic. One way of capturing this myopia is with quasi-hyperbolic discounting. It is well known that such preferences may explain why individuals fail to provide an adequate retirement income for themselves. In this thesis, the quasi-hyperbolic discounting model is applied to a number of other decisions and outcomes related to planning for retirement. There are three main focuses. Firstly, the thesis considers a model where individuals are quasi-hyperbolic discounters over both retirement and saving, and extends the results of Diamond and Köszegi (2003). It argues that mechanisms designed to overcome myopic saving decisions may lead to unplanned early retirement. This may depend on the form of income in retirement -- regular income options such as annuities offer commitment over overconsuming early in retirement, which makes early retirement less desirable to myopic retirees. Secondly, it tests these predictions using a new laboratory experiment. Over a two-month period, participants were asked to attend weekly sessions, and could leave the experiment (or "retire") in any week of their choosing. Part of their payment for attending these sessions was put aside and paid only after they had left. The results indicated that more impulsive individuals left the experiment earlier, both overall and relative to plans made in the first week of the experiment. Finally, this thesis presents a model of rising wages as a forced saving mechanism. Assuming individuals face some borrowing constraints, deferred wages implicitly place some earnings aside until much closer to retirement, when quasi-hyperbolic discounters save a greater fraction of their income, increasing total retirement wealth. It also shows that demand for rising wages should disappear for people with access to more direct saving commitment mechanisms, although when these schemes offer less commitment (due to early withdrawal or early retirement options), a combination of both mechanisms is preferred.